Socialization of Absente Land Prohibition Regulation in Tanara Village, Serang Banten Regency - Amiludin Amiludin; Dwi Nur Fauzi Ahmad (Jurnal Dedikasi Hukum, 2022)
The issue of land does not necessarily concern registration, waiver of rights, or double certificates. Still, it concerns land ownership, which is why many people do not understand that many people exercise waivers to people outside the district. This problem also occurs in tanara village, tanara district, Serang regency, where many local people do not know about this ban, the purpose of this writing is the result of a form of socialization of absente land regulation in tanara village by direct counseling method to the community representing in tanara village office. As for the results of the discussion and the analysis of the absente land, most of the tanara people do not understand the meaning of absente land. The prohibition of absentee land is regulated in article 9 of the Agrarian Basic Law and also article 3, paragraphs 5 and 6 of Government Regulation No. 224 of 1961, which explains that if it is proven that land ownership is absent, the state will take over or revoke its rights and will be distributed to the community following applicable regulations.   Sosialisasi Peraturan Larangan Tanah Absente di Desa Tanara, Kabupaten Serang, Banten Masalah tanah tidak selalu menyangkut pendaftaran, pelepasan hak, sertifikat ganda tetapi menyangkut kepemilikan tanah, itulah sebabnya banyak orang tidak mengerti sehingga banyak orang tidak mengerti sehingga banyak orang melakukan pembebasan kepada orang-orang di luar kabupaten. Permasalahan ini juga terjadi di desa tanara kecamatan tanara kabupaten serang dimana masyarakat setempat banyak yang tidak mengetahui tentang pelarangan ini, tujuan dari penulisan ini adalah hasil dari suatu bentuk sosialisasi pengaturan tanah absente di desa tanara dengan metode penyuluhan langsung ke perwakilan masyarakat di kantor desa tanara. Adapun dari hasil pembahasan dan juga analisis tanah absente, sebagian besar masyarakat tanara belum memahami pengertian tanah absente. Larangan tanah absentee diatur dalam pasal 9 Undang-Undang Dasar Agraria dan juga pasal 3 ayat 5 dan 6 Peraturan Pemerintah No. 224 Tahun 1961 yang menjelaskan bahwa jika terbukti tidak ada pemilikan tanah, maka negara mengambil alih atau dicabut haknya dan akan dibagikan kepada masyarakat sesuai dengan ketentuan yang berlaku